2020
DOI: 10.1002/pssb.202000116
|View full text |Cite
|
Sign up to set email alerts
|

Progress, Challenges, and Rewards in Probing Melt Dynamics, Configurational Entropy Change, and Topological Phases of Group V‐ and Group IV‐Based Multicomponent Sulfide Glasses

Abstract: The observation of reversibility windows (RWs) in binary GexS100−x, AsxS100−x and ternary GexAsxS100−2x glass systems permits constructing a global topological phase diagram in the GeAsS composition triangle. The RW denotes glass compositions for which the enthalpy of relaxation at Tg vanishes, leading to thermally reversing glass transitions. The phase diagram permits delineating glass compositions that are in the flexible phase (FP), intermediate phase (IP), and the stressed rigid phase (SRP) for all terna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 86 publications
(141 reference statements)
3
7
0
Order By: Relevance
“…We then focus on the relationship between molar volume ( V m ) and n c . Indeed, it has previously been observed that ideally connected isostatic glasses (especially chalcogenide glasses) exhibit an optimal space‐filling tendency, which manifests itself as a minimum in molar volume 79–85 . Interestingly, we find that V m exhibits a fair minimum around n c = 2.75, which is close to the isostatic threshold (Figure 8B).…”
Section: Rigidity Diagram Of the Cas Ternary Systemsupporting
confidence: 65%
See 2 more Smart Citations
“…We then focus on the relationship between molar volume ( V m ) and n c . Indeed, it has previously been observed that ideally connected isostatic glasses (especially chalcogenide glasses) exhibit an optimal space‐filling tendency, which manifests itself as a minimum in molar volume 79–85 . Interestingly, we find that V m exhibits a fair minimum around n c = 2.75, which is close to the isostatic threshold (Figure 8B).…”
Section: Rigidity Diagram Of the Cas Ternary Systemsupporting
confidence: 65%
“…Indeed, it has previously been observed that ideally connected isostatic glasses (especially chalcogenide glasses) exhibit an optimal space-filling tendency, which manifests itself as a minimum in molar volume. [79][80][81][82][83][84][85] Interestingly, we find that V m exhibits a fair minimum around n c = 2.75, which is close to the isostatic threshold (Figure 8B). This suggests that the optimal space-filling tendency of isostatic glasses might a be generic feature of the glassy state.…”
Section: Correlations Between Network Topology and Glass/liquid Propertiessupporting
confidence: 55%
See 1 more Smart Citation
“…The inhomogeneities appear on well-defined length scales and can be compared to the formation of intrinsic mesoscopic metastable patterns found in two-fluid I conclude this section with a more general perspective on multiscale landscapes resulting from coexisting short-long-range interactions. In particular, the appearance of glassy filamentary phases in windows of intermediate doping concentration ("intermediate phases") [62,63] is demonstrated in [64,65] as a model of doped 2D anti-ferromagnets. I believe these intermediate phases are very important functionally and should be realized in many materials, including doped TMOs.…”
Section: Hybridized Bands and More Examples Of Short-long-range Competitionsmentioning
confidence: 99%
“…Hence, if atomic configurations are allowed to relax self-consistently in a Coulomb field, the elasticity features above must be recovered. Finally, we note that a quite general framework for intermediate phases can be expressed in a theory describing network adaptability and rigidity transitions based on the degree of lattice connectivity and the number of bonding constraints [62,63,69]. The next material frontiers must include understanding reactive networks.…”
Section: Hybridized Bands and More Examples Of Short-long-range Competitionsmentioning
confidence: 99%